Psychotherapy effects on psychological traits of myocardial infarction patients undergoing sanatorium rehabilitation - R. V. Yusupkhodzhaev; G. G. Efremushkin (Кардиоваскулярная терапия и профилактика, 2008)
Aim. To analyze disease attitude types, psychological protection mechanisms and their dynamics during ericksonian hypnosis, electrosomnotherapy, and audiovisual stimulation in patients with myocardial infarction (MI) undergoing sanatorium rehabilitation.Material and methods. The study included 155 MI patients, aged 32-66 years. Lifestyle index, Heim question naire, and Disease Attitude Type methods were used.Results. Hypnosis improved coping strategies in patients without psychopathologic symptoms or post-MI angina, with arrhythmias, threshold capacity ≥75 Wt, or secondary education. Electrosomnotherapy was effective in participants with higher education and without arterial hypertension. Audiovisual stimulation negatively affected coping strategies. Psychological protection mechanisms remained the same at various treatment stages. Audiovisual stimulation was associated with ergopathic type usage.